Does dietary fluid intake affect skin hydration in healthy humans? A systematic literature review. Issue 3 (2nd February 2018) - Akdeniz, M.; Tomova‐Simitchieva, T.; Dobos, G.; Blume‐Peytavi, U.; Kottner, J.
Abstract: Background: Associations between daily amounts of drinking water and skin hydration and skin physiology receive increasingly attention in the daily life and in clinical practice. However, there is a lack of evidence of dermatological benefits from drinking increased amounts of water. Materials and methods: Pubmed and Web of Science were searched without any restrictions of publication dates. References of included papers and related reviews were checked. Eligibility criteria were primary intervention and observational studies investigating the effects of fluid intake on skin properties in English, German, Spanish or Portuguese language, including subjects being healthy and 18+ years. Results: Searches resulted in 216 records, 23 articles were read in full text, and six were included. The mean age of the samples ranged from 24 to 56 years. Overall the evidence is weak in terms of quantity and methodological quality. Disregarding the methodological limitations a slight increase in stratum corneum and "deep" skin hydration was observed after additional water intake, particularly in individuals with lower prior water consumption. Reductions of clinical signs of dryness and roughness were observed. The extensibility and elasticity of the skin increased slightly. Unclear associations were shown between water intake and transepidermal water loss, sebum content, and skin surface pH. Conclusions: Additional dietary water intake may increase stratum corneum hydration. The underlying biological mechanism for this possible relationship is unknown. Whether this association also exists in aged subjects is unclear. Research is needed to answer the question whether increased fluid intake decreases signs of dry skin.